ABC analysis for layout optimization in logistics distribution centers - Oliveira, Maria Isadora Pinheiro de; Martins, Luís Oscar Silva; Almeida, Kalil Figueiredo; Damm, Djoille Denner; Santos, André de Mendonça (Brazilian Journal of Production Engineering, 2026)
In the current logistics scenario, marked by increasing complexity and competitiveness, the pursuit of efficiency in internal processes has become essential, especially in the presence of operational bottlenecks. In this context, the objective of this article is to optimize the operational processes of a Distribution Center through the application of the ABC Curve integrated with the redesign of the physical layout, aiming to reduce order picking time, improve space utilization, and increase operational productivity. To achieve this objective, a case study was conducted in a real operation, involving the analysis of sales volumes, classification of items according to the ABC Curve, mapping of operators’ movements, and physical reorganization of products within the layout. The study adopts a descriptive methodology with both quantitative and qualitative approaches, including field observations, interviews with employees, and data analysis extracted from the Warehouse Management System. The results indicate that layout reorganization combined with prioritization of high-demand items led to reduced travel times, increased team productivity, and improved operational flow. It is concluded that integrating the ABC Curve with layout redesign represents a practical and efficient solution for reducing operational bottlenecks, optimizing space utilization, and enhancing productivity in warehousing operations.
Keywords: ABC analysis; layout optimization; Distribution center; Inventory management; logistics